1997
DOI: 10.1152/jappl.1997.82.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb skeletal muscle function after 6 wk of bed rest

Abstract: Force, electromyographic (EMG) activity, muscle mass, and fiber characteristics were studied in seven healthy men before and after 6 wk of bed rest. Maximum voluntary isometric and concentric knee extensor torque decreased (P < 0.05) uniformly across angular velocities by 25-30% after bed rest. Maximum quadricep rectified EMG decreased by 19 +/- 23%, whereas submaximum (100-Nm isometric action) EMG increased by 44 +/- 28%. Knee extensor muscle cross-sectional area (CSA), assessed by using magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
256
3
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(293 citation statements)
references
References 24 publications
30
256
3
4
Order By: Relevance
“…Maximal voluntary isometric strength was on average 21% lower in the OA limb than in the healthy limb. Based on previous findings in inactivated healthy subjects (Berg et al 1991(Berg et al , 1997, the greatest loss of strength was expected in the weight-bearing extensor muscles. This appears to have been confirmed around the knee; extension strength was severely reduced while knee flexion strength was not reduced to any significant extent.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Maximal voluntary isometric strength was on average 21% lower in the OA limb than in the healthy limb. Based on previous findings in inactivated healthy subjects (Berg et al 1991(Berg et al , 1997, the greatest loss of strength was expected in the weight-bearing extensor muscles. This appears to have been confirmed around the knee; extension strength was severely reduced while knee flexion strength was not reduced to any significant extent.…”
Section: Discussionmentioning
confidence: 68%
“…MRI, CT) to quantify muscle atrophy due to inactivity, trauma, or disease by CSA or volume only may lead to an underestimation of changes due to undetected alterations in extra-or intramuscular fat or other non-contractile components. Reduced muscle CSA could not fully explain the loss of strength, confirming what is typically shown after unloaded inactivity (Berg et al 1991(Berg et al , 1997. After compensating for non-contractile components in hip extensor muscles using the decreased RD, however, there seems to be no obvious mismatch between weakness and atrophy in the OA limb.…”
Section: Discussionmentioning
confidence: 69%
“…Previous research showed that unloading results in skeletal muscle atrophy. 23,24 For example, knee extensor muscle CSA was reduced by 14% following 6 weeks of bed rest, 23 and the thigh muscle CSA decreased 12% after 6 weeks of unilateral lower limb suspension. 24 The magnitude of skeletal muscle atrophy reported in this study indicates that incomplete SCI could evoke greater disuse than previous reported models of microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MRI was used to quantify skeletal muscle response to unloading and after SCI. [1][2][3][4]23,24 The accuracy of MRI versus dual-energy X-ray absorptiometery (DEXA) in determining skeletal muscle atrophy has been previously investigated showing that DEXA overestimates the proportion of the muscle in fat-free mass after SCI and inaccurately reflects the degree of muscle atrophy compared to MRI. 3 MRI also provides the advantage over computed tomography (CT) by facilitating the acquisition of multiple slices over a single slice commonly used in CT scans, which can inaccurately represent the exact changes in muscle size in response to training or disuse.…”
Section: Discussionmentioning
confidence: 99%
“…Activation interval is useful for evaluation of muscle coordination and effects of the treatment (Benedetti, 2001;Sutherland, 2001), myoelectric fatigue (Merletti et al, 1990; De Luca, 1997), neuromuscular adaptation influenced by age (Merletti and Bonalo, 2008) or muscle inactivity (Edgerton and Roy, 1994;Berg et al, 1997). Studies usually concentrate on basic EMG characteristics in isometric or isotonic muscle activity and on evaluation of the time series of stimulitiming (Turpin, 2011).…”
Section: Introductionmentioning
confidence: 99%